Economic advantages of using bacterial biopreparations in agricultural crops - George Toader; Viorica Chiurciu; Nistor Maierean; Petru Sevciuc; Valentina Filip; Floarea Burnichi; Daniela Trifan; Rîşnoveanu Luxiţa; Cătălin-Ionuţ Enea; Elena-Violeta Toader; Leonard Ilie (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The ecological, genetic, biological approach proposed by agricultural specialists in order to protect plants and crops has a role in reducing the impact of pests through the process of selection and improvement of genetic resources in the processes of planting, development and introduction of biological means to combat pests in agricultural ecosystems. The strategies proposed by the specialists in the agricultural field aim not at the total extermination of the pests from the agricultural crops but at keeping the pest populations at the optimal damage threshold. The most important advantages of these biological processes are those of the evolutionary stability of the crop systems, the ecological stabilization of the pest and crop populations as well as the assurance of a superior quality of the resulting agricultural products.The present paper aims to present the main advantages of using bacterial biopreparations in agricultural ecosystems (research conducted in agricultural research stations in Romania), reducing soil pollution, environmental crops, use of alternative fertilization and cultivation technologies as well as obtaining additional, ecological productions.The aim of this paper is to present the economic advantages of using bacterial biopreparations in agricultural research and development stations, reducing costs in agriculture and the processes that these bacterial biopreparations have on the agricultural ecosystem, the environment and humans and animals.
Keywords: Q56; Q12; Q57; 330; bacterial biopreparations; bioinsecticide; green fertilization technologies; economic advantages